Educational Leadership Sebagai Kekuatan Utama Dalam Menarik Animo Masyarakat Terhadap Pendidikan Islam - Yusuf, M.; Sulistyorini, Sulistyorini; Sujianto, Agus Eko (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
Islamic educational institutions face intense competition in attracting public interest, requiring strong leadership to maintain their sustainability. Educational leadership serves as the primary force in shaping institutional identity, developing strategic policies, and fostering trust among stakeholders. This study explores the role of educational leadership as a key driver in increasing public enthusiasm for Islamic education. Using a library research method with a critical literature analysis approach, this study examines how leadership styles, decision-making processes, and institutional vision influence community perceptions. The findings indicate that effective educational leadership not only enhances institutional credibility but also plays a crucial role in implementing adaptive management strategies. Leaders with strong vision and transformational capabilities can foster innovation, strengthen institutional networks, and improve service quality. This study highlights the importance of leadership models that integrate Islamic values with modern management approaches, ensuring that Islamic education remains relevant and competitive in contemporary society. Strengthening leadership capacity is essential for sustaining institutional growth and expanding the reach of Islamic education.